(untitled) (Bangladesh Journal of Urology, 2025)
Objective: Residual posterior urethral valves (RPUV) after primary ablation can be responsible for the persistence of urinary symptoms and worsening of renal function in children. This study aims to determine the impact of repeat cystoscopy and subsequent re-ablation of residual posterior urethral valves using changes in serum creatinine, uroflowmetry and ultrasonography. Materials and Methods: From April 2022 to August 2023, the study was conducted at the Pediatric Urology Division, Department of Urology, BSMMU, Dhaka. A retrospective review of 74 patients with posterior urethral valves (PUV) was conducted. Of these, 28 patients (37.83%) had symptoms at 03 months like a weak stream (39.3%), straining (10.7%), dribbling (25%) and recurrent attack of fever (3.6%). Among them, 22 patients had no obstructive remnant leaflets and 6 patients (21.4%) had obstructive remnant leaflets in follow-up cystoscopy. Serial serum creatinine measurements (mg/dL), Qmax (ml/s) and ultrasonographic measurements were retrieved and recorded on separate, dated occasions against the date of surgery as follows: before primary valve ablation and at 03-month follow-up. The changing trends in both the serum creatinine, uroflowmetry and the USG changes were analysed for significance against time. The statistical analysis was conducted using SPSS version 26 statistical software. Median with interquartile range for continuous variables and frequency distributions for categorical variables used to describe the characteristics of the total sample. Associations of continuous data were assessed using the Mann-Whitney-U test while associations of qualitative data were assessed by the Fisher Exact test. In both cases, p-value < 0.05 was considered significant. Institutional ethical committee clearance was taken before the commencement of the study. Results: The median age at primary valve ablation was seven years (median [interquartile range] 7.0 [2.0, 10.7]). Repeat cystoscopy was performed in 37.83% of patients, detecting a 21.4% prevalence of residual valves. The initial mean creatinine before the primary ablation was 0.69 mg/dL, with 75% of patients having elevated creatinine levels before surgery. The serum creatinine showed a significant improvement after primary ablation (mean: 0.69 mg/dL to 0.6 mg/dL, p = 0.0001) but minimal improvement after re-ablation (0.6 mg/dL to 0.57 mg/dL, p = 0.68). Preoperatively the median Qmax and PVR were 7.7 and 31.0; which were 11.2 and 25.0 at 03-month follow-up respectively. There was more dilatation in the left renal units (mean: 13.4 mm, 10.9 mm, 8.3 mm) compared to the right (mean: 11.9 mm, 9.7 mm, 8.5 mm). The left renal unit showed significant improvement after both primary ablation (p = 0.04) and re-ablation (p = 0.04). Similarly, the right renal unit showed improvement on both occasions, albeit not statistically significant (p = 0.14 and p = 0.29, respectively). Summarily, a persisting postoperative raised serum creatinine, low Qmax, PVR and hydroureteronephrosis had a significant relationship with residual valves, the sooner the obstruction is resolved entirely, the better the outcome. Conclusions: The prevalence of residual posterior urethral valves after primary ablation was 21.4%, with an improvement in the trend of hydronephrosis and serum creatinine after re-ablation of residual valves. Repeat cystoscopy is therefore effective in the detection of residual valves and has the added benefit of being both diagnostic and therapeutic. Bangladesh J. Urol. 2024; 27(2): 108-114